Applications of Behavior Modification in Organizations: A Review and Critique - Babb, Harold; Kopp, Daniel (Academy of Management Review, 1978)
Behavior modification has many implications for organizations, and yet the recent surge of suggestions for possible applications may go untested. A review and critique of past applications emphasizes critical comments in the areas of metaphysics and ethics, theory, industrial setting and interpretation. Areas for extension of behavior modification are suggested.